Artificial Intelligence in State Management - S. G. Vasin (Управление)
The article is devoted to application of artificial intelligence as a strategic tool to improve governance and economic development in the framework of the established in the country’s digital economy. Based on the analysis of Russian and foreign experience, theory and practice of using a few components of artificial intelligence in public administration proposed a number of recommendations. Only the countries that implemented artificial intelligence into the system of state management will be able to compete on the international stage, will be able to withstand the various internal and external threats.